TV viewing time is associated with increased all-cause mortality in Brazilian adults independent of physical activity - Turi, B. C. [UNESP]; Monteiro, H. L. [UNESP]; Lemes, R. [UNESP]; Codogno, J. S. [UNESP]; Lynch, K. R. [UNESP]; Asahi Mesquita, C. A. [UNESP]; Fernandes, R. A. [UNESP] (Wiley, 2018)
The purpose of this study was to investigate the association between television (TV) viewing and all-cause mortality among Brazilian adults after 6 years of follow-up. This longitudinal study started in 2010 in the city of Bauru, SP, Brazil, and involved 970 adults aged ≥50 years. Mortality was reported by relatives and confirmed in medical records of the Brazilian National Health System. Physical activity (PA) and TV viewing were assessed by the Baecke questionnaire. Health status, sociodemographic and behavioral covariates were considered as potential confounders. After 6 years of follow-up, 89 deaths were registered (9.2% [95% CI=7.4%-11%]). Type 2 diabetes mellitus was associated with higher risk of mortality (P-value=.012). Deaths correlated significantly with age (ρ=.188; P-value=.001), overall PA score (ρ=−.128; P-value=.001) and TV viewing (ρ=.086; P-value=.007). Lower percentage of participants reported TV viewing time as often (16%) and very often (5.7%), but there was an association between higher TV viewing time (“often” and “very often” grouped together) and increased mortality after 6 years of follow-up (P-value=.006). The higher TV viewing time was associated with a 44.7% increase in all-cause mortality (HR=1.447 [1.019-2.055]), independently of other potential confounders. In conclusion, the findings from this cohort study identified increased risk of mortality among adults with higher TV viewing time, independently of PA and other variables.
Keywords: Brazil; epidemiology; mortality; public health; sedentary behavior; television